3D meso-scale modelling of the bonding failure between corroded ribbed steel bar and concrete. (1st April 2022) - Liu, Mengjia; Jin, Liu; Chen, Fengjuan; Zhang, Renbo; Du, Xiuli
Highlights: A 3D mesoscopic model for corroded rebar-concrete interface behavior is developed. The surface characteristic of corroded crescent ribbed bar is considered in detail. The bond failure mechanism of steel rebar-concrete interface was clearly revealed. A modified model was developed to describe the bond stress-slip relationship. Abstract: Subjected to a corrosive environment, the macroscopic behavior of reinforced concrete structures is closely related to the bond property between rebar and concrete. For assessing the material performance and evaluating the nonlinear bond behavior of the interface between corroded ribbed rebar and concrete, and finally revealing the meso -mechanical failure mechanism of the reinforced concrete structure, we propose a 3D mesoscopic model in the current paper. The following elements that may influence the macroscopic behavior of the reinforced concrete are considered in the model: (1) the friction resistance and the mechanical interaction between corroded ribbed rebar, rust and concrete (2) the surface characteristic of threaded ribbed bar. The proposed mesoscopic model allows us to assess the influences of corrosion on the bond performance of corroded reinforced concrete through a two-stage analysis: after considering the expansive behavior of the reinforced concrete in the model, we apply a pull-out force on the corroded rebar to evaluate the bond-slip behavior between the corroded rebar and concrete. For validating our model, we compare the failure patterns and corroded bond stress-slip curves calculated by the model and obtained by experimental means and found a good consistency between them. Finally, a modified model was developed to describe the corroded bond stress-slip relationship. It has been found that when relative slip is applied, the concrete continues to crack along pre-existing cracks caused by corrosion products until the concrete splitting failure accorded. With the increase of corrosion level, the shape of the bond stress-slip curve is similar with a significantly degradation of the bond strength and peak slip, especially at small corrosion levels. Through comparing the proposed modified formula with the existing test data, one can find that the proposed modified formula can effectively characterize the corroded bond stress-slip relationship between deformed rebar and concrete.